Understanding the Impact of Fibromyalgia on Men: Findings From a Nationwide Survey. Issue 4 (July 2018) - Muraleetharan, Daenuka; Fadich, Ana; Stephenson, Colin; Garney, Whitney
Fibromyalgia (FM) is a serious condition that affects approximately four million people in the United States, and is underdiagnosed in men. The objective of this study was to understand this phenomenon by examining multiple impacts of fibromyalgia on men in regard to interactions in society and the U.S. health system. A qualitative survey was administered to 1, 163 respondents both online and in-person in Tennessee, Virginia, Maryland, and Washington, DC. Thematic analyses of the survey responses suggest that men with FM have negative experiences with (1) physical and mental health, (2) quality of life, (3) relationships, and (4) careers as a result of FM. Interactions with health-care providers were deterred by (1) potential for misdiagnosis or dismissal of symptoms, (2) stigma of having a condition primarily affecting women, (3) differences in treatment of men and women with FM, and (4) need for health education resources. These findings dictate a need to improve communication between health-care providers and male FM patients.